Seed Systems, Science and Policy in East and Central Africa - Technical Centre for Agricultural and Rural Cooperation (CTA / ASARECA, 2014)
Unique in terms of the insights it provides into the various seed systems that exist in Sub-Saharan Africa, this important publication examines how quality seeds can be made available and Africa can increase its share of the global seed trade. A direct output of materials from the CTA/ASARECA ‘Seed Science and Policy Learning’ writeshop, the text also presents information on the policy environment. It includes challenges faced and contributions made by governments, universities, the private sector, farmers, women’s groups and regional organisations on these issues.